Theatricality and the Canonization of Performance: A Foreword to Josette Feral's Article - R. Malkin, Jeanette (MiKAN, 2006)
This article examines the diachronic changes in Josette Feral's thinkingabout theatricality and its relation to performance, from her first articleon the subject in 1985, up until 2002. These changes are viewedIXin light of the developments in theatre research over the last threedecades in the United States and Europe, and in particular in light ofthe academic canonization of Performance Studies. While elaboratingupon the meaning of her strategic move from an "Americano-centric"ideology toward a more "European" aesthetic discourse, Malkin drawscorrelations between current trends in performative culture and early20th century European, and especially German, avant-garde theatretheory. The "Foreword" presents Feral's axis of thought - theatrical/performative - as dynamic and sensitive to cultural developments.Feral's original binary position developed into a synthesis that allowsher to encompass both terms under the enlarged, Kantian-inflectedcategory of "theatricality". In the end Feral posits performance - whichshe had originally described as "a deconstruction of theatrical codes"- as one of the fundamental components of theatricality itself. Thistheoretical "shift" has disciplinary implications since it questions thebenefit of the academic separation between theatre and performancestudies. Malkin consequently contends that the development inFeral's theoretical approach to performance has been parallelled bysimultaneous shifts in both its artistic practice, as well as in its changingacademic status.